AWARENESS ON RABIES AMONG DENTAL STUDENTS - Subaraman,; Ganapathy, Dhanraj; Sasanka, Keerthi (International Journal of Psychosocial Rehabilitation, 2025)
Rabies awareness in the dental students is very important and is very important in creating effective preventive measures in the public. Rabies Is a fatal viral disease that can infect all the mammals, but dogs are the main source of human infections.To evaluate the knowledge and awareness of the rabies among dental students.This was a questionnaire based observational cross sectional type of study. The study population consisted of dental students from SaveethaDental College. A self designed questionnaire of 10 questions was framed based on the knowledge and awareness of rabies given the dental students using an online survey mode.The survey contained a setof 10 questionseliciting awareness aboutrabies.The responses were collected and analysed.83% of students were aware that the rabies is fatal once the symptoms appeared .74% of students were aware that the rabies is a viral disease.68% of students were aware that the rabies is primarily transmitted through saliva.69% of students were aware that rabies are more common in dogs.41% of students were aware about the incubation time.73% of students were aware about the symptoms of rabies. The study concluded that the knowledge on theawareness of rabies among dental students is moderately adequate.